Makna Kata Arkais Pada Buku Palsafah Pakaian Penghulu Jo Pidato Aluo Pasambahan Adat Minangkabau - Rizki Eka Putra; Retty Isnendes; Eri Kurniawan (Journal on Education, 2024)
Although there have been many studies that discuss meaning, both in Indonesian and in Minangkabau, no research has been found that examines the lexical meaning and cultural meaning of Minangnese archaic words in pasambahan. This is important to study because pasambahan contains advice, manners, cultural values, and educational values that have existed for a long time and must be passed down. Therefore, there is a need for research that explores the lexical meaning and meaning of the cultural context contained in archaized words in pasambahan. This research uses a qualitative design. The source of data comes from a study entitled Identification of Archaic Words in the Book of the Philosophy of Penghulu Clothing Jo Pidato Aluo Pasambahan of Minangkabau Custom. The data was tested in an interview with the author of the book. The results show that of the 34 archaic words studied, 26 words have lexical meaning and cultural meaning, and 8 words only have lexical meaning. The cultural meaning contains advice to tribal leaders, advice for daily life, a description of Minangkabau nature, a description of Minangkabau traditional houses, and manners, advice on religion, and advice on decision-making.